Hydrothermal growth of Fe2O3 nano/micro-rods on Fe foil for Cr(VI) removal. (2019) - Chew, B.K.; Jun, H.K.; Lockman, Z.; Razak, K.A.; Ng, C.Y.
Abstract: In this work, the effect of hydrothermal duration on the synthesis of Fe2 O3 rods on Fe foil was studied. The hydrothermal process was performed at 100 °C for 6–15 h. The fabricated samples were then annealed at 300 °C for 2 h. Iron oxide nano/micro-rods (diameter: 50–250 nm) which comprised of γ-Fe2 O3 and α-Fe2 O3 phases were successfully grown on the Fe foil after the hydrothermal process. Rise in hydrothermal duration resulted in more growth of rods on the Fe foil. After 12 h, the entire Fe substrate was fully covered with Fe2 O3 rods. Hydrothermal duration of 12 h was found to be sufficient for Fe2 O3 rod growth by achieving >99% of Cr(VI) removal in 50 min.